2021
DOI: 10.1016/j.waojou.2021.100551
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on asthma symptoms and management: A prospective analysis of asthmatic children in Ecuador

Abstract: Background Asthma affects up to 33% of children in Latin American settings. The ongoing COVID-19 pandemic has had a significant impact on access to and use of health services. We aimed to evaluate the impact of the COVID-19 lockdown on asthma exacerbations, medical facility visits, and use of asthma medications in children. Methods We used data from a prospective cohort of 213 children aged 5–17 years in 3 Ecuadorian cities and analysed the impact of the COVID-19 lockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…Heterogeneity test analysis suggested that there was heterogeneity ( I 2 = 75%, p = 0.007) (Figure 2A). Sensitivity analysis suggested that after removing Ochoa‐Avilés et al's research, 20 the heterogeneity disappeared ( I 2 = 0%, p = 0.75). The random effects model was used.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Heterogeneity test analysis suggested that there was heterogeneity ( I 2 = 75%, p = 0.007) (Figure 2A). Sensitivity analysis suggested that after removing Ochoa‐Avilés et al's research, 20 the heterogeneity disappeared ( I 2 = 0%, p = 0.75). The random effects model was used.…”
Section: Resultsmentioning
confidence: 92%
“…Ten studies, [14][15][16][17][18][19][20][21][22][23] with 22,159 subjects were included for the final meta-analysis. The sample size of the studies ranged from 16 to 18,912.…”
Section: Study Characteristicmentioning
confidence: 99%
See 2 more Smart Citations
“…12 La carencia de exacerbaciones graves que hayan requerido asistencia hospitalaria alude que no existe relación con la infección por SARS-CoV-2/COVID-19 en asma. 13 Los síntomas del SARS-CoV-2/COVID-19, incluyen tos, disnea y opresión en el pecho, condiciones difíciles de distinguir en una exacerbación grave del asma, lo que podría dificultar el diagnóstico y un tratamiento oportuno. 14 No obstante, las sibilancias es un síntoma generalmente no asociado al SARS-CoV-2/COVID-19.…”
Section: Manifestaciones Clínicasunclassified